Safe Asset Demand, Global Capital Flows and Wealth Concentration - Kim, Taehoon (IMF Working Papers; Working Paper ;, 2021)
The US economy is often referred to as the "banker to the world," due to its unique role in supplying global reserve assets and funding foreign risky investment. This paper develops a general equilibrium model to analyze and quantify the contribution of this role to rising wealth concentration among American households. I highlight the following points: 1) financial globalization raises wealth inequality in a financially-developed economy initially due to foreign capital pressing up domestic asset prices; 2) much of this increase is transitory and can be reversed as future expected returns on domestic assets fall; and 3) despite the low-interest-rate environment, newly accessed foreign capital provides incentives for affluent households to reallocate wealth toward risky assets while impoverished households increase their debt. Wealth concentration ensues only if this rebalancing effect is large enough to counteract diminished return on domestic assets. Quantitative analysis suggests that global financial integration alone can account for a third to a half of the observed increase in the current top one percent wealth share in the US, but indicates a possible reversal in the future.